Inside Back Cover Image, Volume 95, Number 1, January 2023. Issue 1 (5th January 2023) - Wettstein, Lukas; Immenschuh, Patrick; Weil, Tatjana; Conzelmann, Carina; Almeida‐Hernández, Yasser; Hoffmann, Markus; Kempf, Amy; Nehlmeier, Inga; Lotke, Rishikesh; Petersen, Moritz; Stenger, Steffen; Kirchhoff, Frank; et al.
Abstract : Inside Back Cover Caption : The cover image is based on the Research Article Native and activated antithrombin inhibits TMPRSS2 activity and SARS‐CoV‐2 infection by Lukas Wettstein et al., https://doi.org/10.1002/jmv.28124 . Image Credit: Yasser Almeida‐Hernández.